Experimental Investigation of Forced Convection Heat Transfer in Open Cell Copper Fins - Ali, Issam Mohammed; Mussa, Munther Abdullah; Mustafa, Mustafa Mahdi (Al-Nahrain Journal for Engineering Sciences, 2017)
Recently, major part of convection heat transfer researches focus on increasing fins efficiency by increasing thermal performance for the same fin volume. Metal foam is a promising way to achieve this aim. Performance analysis has been carried out to investigate the heat transfer characteristics of copper fin foam samples. The samples have been compared with the solid metal fin heat transfer. A forced convection heat transfer had been applied to a four specimens. An electrical heater heats up the fins, which are subjected to a stream of the ambient air driven by a blower fan as heat dissipated. The heat flux had been fixed along the tests with three different air velocity used; the forced heat convection had been simulated. The pores density of copper fin foam is varied in the range of 10, 20 & 40 pores per inches (PPI). Thermal performance of copper fin foam has been evaluated in terms of average Nusselt number and thermal resistance of heat sinks. The increasing in the heat transfer rate and average Nusselt number when used metal foam has been found in the range of 36-133 % compare to solid copper. Furthermore, it has been proven that this increment reaches the maximum value for a given PPI even when raise the air velocity.